STUDI KOMPARASI HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DAN ROTATING TRIO EXCHANGE (RTE) PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 10 PEKANBARU - Risaftia Andini; Johni Azmi; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of research was to know whether there was significant differences for students achievement between the application of cooperative learning model type Teams Games Tournament (TGT) and Rotating Trio Exchange (RTE) on the colloid subject in class XI Science Senior High School 10 Pekanbaru. The kind of research was the experiment research with Randomized Control Group Pretest-Posttest Design. The pupolation in the research were all of students in class XI Science Senior High School 10 Pekanbaru. There were three classes as sample of research which were choiced randomly by using normality and homogenity test. Class XI Science 1 as the experiment 1 (TGT), Class XI Science 3 as the experiment 2 (RTE) and XI Science 2 as the Control (STAD). The data analysis technique used to test hypothesis was the ANOVA one way and Scheffe multiple comparison.The result of data analysis used Scheffe multiple comparison show that the average difference of experiment 1 and experiment 2 lower than Scheffe value (1,67<4,52), it’s mean there was no significant differences of the student’s achievement between the application of cooperative learning model type Teams Games Tournament (TGT) and Rotating Trio Exchange (RTE) on the colloid subject in class XI Science Senior High School 10 Pekanbaru.Key Words: Comparative Study, Student’s Achievement, Teams Games Tournament (TGT), Rotating Trio Exchange (RTE), Colloid.